Hasil Temuan Suspect BTA Sebelum dan Sesudah Program Ketuk Pintu oleh Kader Berdasarkan Kualitas Sampel Dahak - Dede Sumiati; Teguh Budiharjo (Poltekkes Kemenkes Semarang, 2019)
The purpose of this study was to determine the difference between the findings of BTA suspect before and after the door knock program by cadres in 2017 based on the quality of sputum samples in the UPTD Kroya II Community Health Center. The type of research conducted was quantitative descriptive. Data analysis used a different test of Independent t-test (bivariate) with the help of SPSS 24. The results showed 226 suspect numbers of TB with BTA + findings before the program knocked on the door by cadres as much as 29.2%, after the program the number of suspects was 367 people with BTA + findings were 3.3%. This shows that there are differences in the findings of BTA suspect before and after the door knock program by cadres in 2017 based on the quality of sputum samples in the UPTD Kroya II Health Center.